PROCESSES AND SYSTEMS of avionics technical operation as Markov AND Semimarkov processes MATHEMATICAL MODELS - S. V. Kuznetsov (Научный вестник МГТУ ГА)
Technical operation of the aircraft and its avionics is investigated as a process with the succession of states of operation. The models of the processes and systems of technical operation of avionics in the form of stationary and non-stationary Markov chains of the first and higher order are proposed. There are examples of the processes for two states of operation - able to work and disabled states.